Comparative Study of Information System Governance Frameworks: Foundations for IT Risk Management Using COBIT 2019 and ITIL - Sholeh, Moch. Badrus; Pramudya, Naufal Daffa (Jurnal Transformatika, 2025)
In this study, COBIT 2019 and ITIL V4 are compared in the context of managing IT risk. Through systematic literature review (SLR), the theoretical and practical foundations of both frameworks are evaluated. COBIT 2019 offers a structured approach, while ITIL emphasizes adaptive operational practices. Analysis of strengths and weaknesses helps organizations choose an approach that aligns with their strategic objectives. With this understanding, organizations can enhance their ability to manage IT risks and achieve business goals effectively.